The influence of human resource development challenges on public health service delivery in Mangaung - Tsosane, M. A. (University of the Free State, 2020)
Purpose – It is a constitutional mandate that all three spheres of government should provide quality services to citizens of South Africa. There has been an increasing demand from the public for quality health service delivery as shown in the high number of public protests against poor health service delivery. It, therefore, appears as if the National, the Pelonomi Regional, and the Universitas Academic Hospitals have been overwhelmed by having a financial shortfall that had a direct influence on the development of administrative staff, whose development was neglected. The study aims to determine the human resource development (HRD) challenges that the administrative staff of the National, Pelonomi Regional and the Universitas Academic Hospitals face in its mandate to provide efficient, effective and economical service delivery. Quality health services can only be provided if there are equipped public servants who can perform their job well. Public servants’ ability depends on the extent to which they are developed through HRD. Research design, approach, and method - The study employed a qualitative research design. Focus group discussions and semi-structured interviews were used as qualitative research instruments. Focus group discussions were conducted with seventy-one (71) administrative staff and semi-structured interviews consisted of six (6) staff responsible for the management of HRD. Findings – The paper concludes that the FSDoH is still faced with the problem of a skills audit and insufficient budget allocations. Therefore, there is a dire need by the FSDoH to acquire skilled HRD professionals or to upgrade their skills and knowledge to meet the requirements of the now changing Public Sector. Hence, to realize the need and value of HRD, FSDoH needs to see the importance of continuous education and training towards the development of administrative staff. The more reason and need to employ effective public servants to provide quality health service delivery and accomplish the department’s goals. Practical implications – FSDoH officials, as well as other stakeholders such as politicians, have an important role to play in understanding the value of HRD in public health service delivery. Therefore, a serious internal organizational HRD framework is required that will enhance the staff’s ability to perform and deliver quality health services to the citizens. Contribution – This thesis should be of significance to each administrative staff member to promote the use of HRD as a tool to improve service delivery in the FSDoH. It is also hoped that this will encourage scholars to investigate the relevance of HRD in service delivery within the public health institutions.
Dissertation (M.P.A. (Public Administration))--University of the Free State, 2020
Keywords: Human Resource Development; Human Resource Management; Service delivery; Department of Health; Administrative staff